Characteristics of Briquettes Produced from Corn Cob and Corn Stalk Charcoal Blends - David Mangallo; Thomas Pagasis; Bertha Mangallo (FMIPA Universitas Papua, 2026)
Corn cobs and corn stalks represent abundant agricultural residues with significant potential for conversion into solid biofuels. This study aimed to evaluate the physicochemical characteristics of briquettes produced from varying proportions of corn cob charcoal and corn stalk charcoal. Carbonization was conducted through pyrolysis using a modified oil-drum reactor. The resulting char was pulverized and sieved to 60 mesh to ensure particle uniformity prior to briquetting. A 5% tapioca starch solution was used as a binding agent, and briquettes were formed using a hydraulic press in a honeycomb configuration (4-inch diameter, 16 central perforations). Five different charcoal composition ratios were prepared and analyzed. Proximate analysis revealed moisture content ranging from 4.68% to 5.71%, ash content from 12.27% to 17.23%, volatile matter from 16.24% to 21.62%, and fixed carbon from 56.47% to 65.78%. The calorific value varied between 5,138 and 5,274 cal/g. The results demonstrate that blended corn cob and corn stalk charcoal briquettes exhibit favorable fuel properties and potential applicability as sustainable alternative energy sources.